Challenges of Strategic Stability Amongst Littoral Powers of the Indian Ocean Region - Zahir Kazmi (CISS Insight Journal, 2024)
The Indian Ocean Region holds strategic significance due to its historical and economic importance. However, it faces strategic instability due to increasing great power contestation and disputes between its littoral Nuclear Weapon States, Pakistan and India. Modernization of nuclear and conventional forces, risk-taking military doctrines, and unregulated military applications of emerging technologies are among the sources of this instability. This paper reinterprets the concept of strategic stability and discusses the challenges of maintaining it in the IOR. It highlights the role of India’s growing power ambition, the widening gap in nuclear and conventional power asymmetries between Pakistan and India, and the US-led policy to build India as a counterweight to China. It warns that these factors may turn India into a source of insecurity. India’s nuclear enterprise, which fuels its global power ambition, is outgrowing its security needs against China and Pakistan. It suggests that the US may need to counteract India’s growing capabilities and behavior to maintain the post-Second World War rules-based order. Additionally, it warns that if India can play arch-rivals and claim strategic autonomy today, it may work against American interests once its dependence reduces.